Cocaine: An Updated Overview on Chemistry, Detection, Biokinetics, and Pharmacotoxicological Aspects including Abuse Pattern - Roque Bravo, Rita; Faria, Ana Carolina; Brito-da-Costa, Andreia Machado; Carmo, Helena; Mladěnka, Přemysl; Dias da Silva, Diana; Remião, Fernando; On Behalf Of The Oemonom Researchers (Toxins, 2022)
Cocaine is one of the most consumed stimulants throughout the world, as official sources report. It is a naturally occurring sympathomimetic tropane alkaloid derived from the leaves of Erythroxylon coca, which has been used by South American locals for millennia. Cocaine can usually be found in two forms, cocaine hydrochloride, a white powder, or 'crack' cocaine, the free base. While the first is commonly administered by insufflation ('snorting') or intravenously, the second is adapted for inhalation (smoking). Cocaine can exert local anaesthetic action by inhibiting voltage-gated sodium channels, thus halting electrical impulse propagation; cocaine also impacts neurotransmission by hindering monoamine reuptake, particularly dopamine, from the synaptic cleft. The excess of available dopamine for postsynaptic activation mediates the pleasurable effects reported by users and contributes to the addictive potential and toxic effects of the drug. Cocaine is metabolised (mostly hepatically) into two main metabolites, ecgonine methyl ester and benzoylecgonine. Other metabolites include, for example, norcocaine and cocaethylene, both displaying pharmacological action, and the last one constituting a biomarker for co-consumption of cocaine with alcohol. This review provides a brief overview of cocaine's prevalence and patterns of use, its physical-chemical properties and methods for analysis, pharmacokinetics, pharmacodynamics, and multi-level toxicity.
Keywords: Ethanol; toxicity; crack; dopamin; drug abuse; cocaine hydrochloride; drug analysis; Dopamine; kokain; pharmacokinetics; sympathomimetics; ethanol; Cocaine; pharmacodynamics